Fecal Incontinence: A Devastating Pathology - Martínez, Bertha Zenaida Acevedo; Sánchez, Morelos Adolfo García; Rodríguez, Alejandro Giovanni Hernández; González, Joel Iván Cruz; Solis, Karla Ixchel Contreras; Aviléz, José Alberto Chamú; Benítez, Xochitl Citlalli Valderrama; Larios, Zuri Sadai Grez; Jiménez, Gema Ariadna Ramos; Piña, Óscar Escalante (British Journal of Healthcare and Medical Research, 2024)
Introduction: Fecal incontinence is the lack of control or involuntary loss of fecal matter; its etiology is multiple and confusing. Objective: 18 years of experience in the Colon and Rectal Surgery service in the treatment of patients suffering from fecal incontinence. Method: longitudinal, retrospective, observational and descriptive study. Records of patients surgically treated for fecal incontinence clinically with anatomical deletion in the Colon and Rectal Surgery services of three hospitals are reviewed. Results: Of 341 patients with fecal incontinence, of which 225 were treated with rehabilitation and non-surgical medical therapy, the rest of the group, which were 116 patients with fecal incontinence, were managed surgically. Anal plasty with sphincter restitution was performed in 113 patients, representing 97.41%, and in 3 cases the Parks posterior repair surgical technique was performed in 2.58%. Discussion: Fecal incontinence has been clinically classified by severity in various ways. Likewise, conservative and surgical management is varied, transitory and achieves a great improvement in symptoms, biomaterial injectables and surgical treatment that manages to cure the disease. Conclusions: Specialized surgery is currently the most cost-effective, most efficient and effective solution to treat fecal incontinence, which is devastating, since it exposes overwhelming success rates and provides a quality of life very close to normal to the patient.